Prediction of kinetic models for drying lemon balm leaves in a convective dryer (Research, Society and Development, 2020)
The present work aimed to evaluate the adjustments to the mathematical models of the drying kinetics of lemongrass leaves in a convective dryer at 40, 55 and 70 ° C, with drying air velocities of 1.0, 1.5 and 2.0 m / s by factorial design 22 + 3 experiments at the central point. The fresh leaves were subjected to chemical, physical and physicochemical characterization. The drying kinetics was performed in a convective dryer, with adjustments for four mathematical models, being considered as fit quality criterion, the determination coefficients (R2) and the mean square deviations (DQM). After the drying tests, one can highlight the three test conducted at a temperature of 40 ° C and a speed of 1.0 m / s, presenting higher yield and lower water content, the resulting powder was subjected to analysis of: granulometry , water content, water activity, ashes, wettability, hygroscopicity, solubility, specific mass, specific compaction mass, Hausner factor, compressibility index, color, flavonoids, total and b chlorophylls, carotenoids and tannins. The models presented satisfactory adjustments to the drying kinetics, with R²> 99.0% and DQM